Pregnancy-related anxiety and subjective sleep complaints during pregnancy - Tyrylahti, Kati (fi=Turun yliopisto|en=University of Turku|, 2018)
Sleep complaints and reports of anxiety are relatively common among pregnant women. Currently the potential adverse effects of maternal prenatal anxiety on the future child are becoming better acknowledged, and there are studies highlighting the particularly adverse consequences of pregnancy-related anxiety. Similarly, there are studies showing the risks associated with sleep disturbance during pregnancy. Although the relationship between sleep disturbance and affective dysregulation is well established in general population, more understanding is needed to better detect and appropriately treat both emotional and sleep related problems during pregnancy. The purpose of this study was to examine the associations between pregnancy-related anxiety, subjective insomnia symptoms and excessive daytime sleepiness, as well as to identify factors associated with the change in pregnancy-related anxiety from mid to late pregnancy. The present study is part of the FinnBrain research project, a large ongoing birth cohort study based in Southwestern Finland. Mothers filled questionnaires at three time points during pregnancy: pregnancy-related anxiety was reported at gestational weeks 24 and 34, subjective insomnia symptoms and excessive daytime sleepiness were reported at gestational weeks 14, 24 and 34, and background information was collected at gestational week 14. The current sample consists of 2202 pregnant women with all relevant data available. The results provide support for an association between pregnancy-related anxiety and sleep disturbances during pregnancy. Higher levels of pregnancy-related anxiety were associated with more frequent sleep complaints. These associations were found consistently both within and across the time points. In addition, pregnancy-related anxiety was found to increase together with daytime sleepiness, while similar association was not found with subjective insomnia symptoms. The effect of maternal age, education level, parity or presence of physical and/or mental illness was controlled for. These finding have not been reported before. The results of this study add to the growing body of literature recognising the importance of sleep and affective wellbeing during pregnancy for both mother and the future child. In clinical work these findings may be used to better identify mothers prone to sleep disturbance and/or feelings of anxiety, as well as to develop interventions promoting sleep and/or psychological wellbeing in pregnant women.